An analysis of intertemporal and cross-sectional determinants of earnings response coefficients - Collins, Daniel W.; Kothari, S.P. (Journal of Accounting and Economics, 1989)
Stock pride change associated with a given unexpected earnings change (the earnings response coefficient) exhibits cross-sectional and temporal variation. We predict and document evidence that the earnings response coefficient is a function of riskless interest rates and the riskiness, growth and/or persistence of earnings. The earnings response coefficient also varies cross-sectionally with the holding period return interval. Collectively, our results explain the previously reported differential earnings response coefficient with respect to size. Moreover, by including the factors noted above, the empirical specification of the earnings/returns relation is significantly improved.